2020
DOI: 10.1111/nmo.13914
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota changes induced by microencapsulated sodium butyrate in patients with inflammatory bowel disease

Abstract: Background Butyrate has shown anti‐inflammatory and regenerative properties, providing symptomatic relief when orally supplemented in patients suffering from various colonic diseases. We investigated the effect of a colonic‐delivery formulation of butyrate on the fecal microbiota of patients with inflammatory bowel diseases (IBDs). Methods In this double‐blind, placebo‐controlled, pilot study, 49 IBD patients (n = 19 Crohn's disease, CD and n = 30 ulcerative colitis, UC) were randomized to oral administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 54 publications
0
69
0
1
Order By: Relevance
“…As a matter of fact, BLM has a strong anti-inflammatory and antioxidant activity, as well as a protective effect on the gut barrier; indeed, butyrate is an energy source for intestinal epithelial cells and contributes to their integrity [27]. As recently suggested, BLM was able to influence gut microbiome composition reducing inflammation of the colon [18].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As a matter of fact, BLM has a strong anti-inflammatory and antioxidant activity, as well as a protective effect on the gut barrier; indeed, butyrate is an energy source for intestinal epithelial cells and contributes to their integrity [27]. As recently suggested, BLM was able to influence gut microbiome composition reducing inflammation of the colon [18].…”
Section: Discussionmentioning
confidence: 90%
“…IBD patient's microbiome was compared to that of 18 healthy volunteers. It was found that exogenous butyrate increased butyrate-producing bacteria, which in turn increased endogenous butyrate production, contributing to gut homeostasis [18]. Finally, in patients with active UC, administration of butyrate in association to standard therapy demonstrated a significant improvement of inflammatory parameters [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 98%
“…We thank Sitkin et al for their interest on our study and their valuable comments. 1 The authors speculated that the microbiota changes Slowly, as a very complex and hardly decodable puzzle, the therapeutic signaling of butyrate supplements is taking shape, but further larger studies are needed to confirm the usefulness and clinical efficacy of supplementing butyrate in patients with IBD.…”
Section: Reply Letter To "Oral Butyrate Modulates the Gut Microbiotamentioning
confidence: 99%
“…Short‐chain fatty acids (SCFAs) are the main products of bacterial fermentation of undigested and unabsorbed carbohydrates in the intestine 3 . SCFAs are the main energy source for colonic epithelial cells, regulating gut barrier functions and local immune defenses 3 . Among the SCFAs, butyric acid has anti‐inflammatory and intestinal regenerative effects and administration of sodium butyrate to patients with inflammatory bowel disease changes the gut bacterial composition and induce the growth of butyric acid‐producing bacterial genera 3 …”
Section: Introductionmentioning
confidence: 99%